SOCIAL POLICY, STATE, AND ‘SOCIETY’ - Jessop, Bob (SER Social, 2014)
This contribution explores the relations among social policy, the state and ‘society’ in the light of recent changes in capitalist social formations, including the increasing integration of the world market and the increasing significance of ‘world society’ as the ultimate horizon of communication, calculation, and policy deliberations. It builds on my earlier work on welfare state restructuring but updates it in four ways. First, it provides stronger foundations for analyses of welfare regimes in the nature of capitalism, looking beyond a general critique of the capitalist mode of production to consider specific configurations of capitalist social formations and their insertion into the world market. Second, it extends my earlier work beyond the economies of Atlantic Fordism and their crises to include export-oriented economies and developmental states and the differential implications for welfare regimes of knowledge-based economies and finance-dominated regimes as potential bases of post-Fordist accumulation. Third, especially in relation to finance-dominated accumulation, it considers the problematic status of the welfare state and/or social policy in neoliberal regimes that are strongly inserted into a competitive world market. And, fourth, it addresses the status of ‘global social policy’ as a response to the integration of the world market and the emergence of ‘world society’. The contribution ends with some general conclusions about the study of welfare regimes.